Genotoxic and antigenotoxic assessment of four newly synthesized dihydropyridine derivatives - Turhan, Kadir; Ozturkcan, S. Arda; Turgut, Zuhal; Karadayi, Mehmet; Aslan, Ali; Gulluce, Medine (SAGE PUBLICATIONS INC, 2014)
The current study aims to determine the genotoxic and antigenotoxic potential of four newly synthesized dihydropyridine derivatives using Escherichia coli WP2 and Ames/Salmonella bacterial reversion assay systems. The bacterial mutant tester strains, E. coli WP2uvrA with a point mutation and Salmonella typhimurium TA1537 with a frameshift mutation, were used to determine genotoxic potentials of the test compounds. To determine antigenotoxic potentials of the test compounds, the same strains were also used together with positive mutagens N-methyl-N-nitro-N-nitrosoguanidine (MNNG) for E. coli WP2uvrA and 9-aminoacridine (9-AA) for S. typhimurium TA1537. According to the results, neither of the test compounds showed significant genotoxic activity on both tester strains at the tested concentrations. However, except compound 4, all the test compounds showed significant antigenotoxic activity on MNNG- or/and 9-AA-induced mutations. The inhibition rates of mutagenesis ranged from 27.0% (compound 2: 2.5mM/plate) to 65.0% (compound 2: 0.5mM/plate) for MNNG and from 30.6% (compound 2: 2mM/plate) to 58.5% (compound 1: 1mM/plate) for 9-AA genotoxicity. According to these results, it is concluded that all the test compounds do not have a mutagenic potential on the bacterial strains at the tested concentrations, and some of them have antigenotoxic potentials against MNNG- and 9-AA-induced mutagenesis.
Keywords: Dihydropyridine; genotoxicity; antigenotoxicity; bacterial reverse mutation test; MNNG; 9-aminoacridine; CALCIUM-CHANNEL BLOCKER; 1,4-DIHYDROPYRIDINE DERIVATIVES; MUTAGENICITY ASSAY; ESCHERICHIA-COLI; SODIUM-AZIDE; CEREBROCRAST; INHIBITORS; DESIGN; ACID; MUTAGENESIS; Public, Environmental & Occupational Health; Toxicology